An analysis of faculty members’ profiles of Indian Institute of Science, Bengaluru, with special reference to the Indian research information network system - Prakash, M.; Arumugam, J. (University of Jaffna, 2022)
This paper describes the analysis of the Indian Institute of Science, Bengaluru faculty profile as reflected in the Indian Research Information Network System (IRINS). A Research Information System is essential for any institution to create a database of the faculty research profile and monitor the quality of publications to various extents. This study highlights the number of faculty members in all the de partments of the Indian Institute of Science, Bengaluru, involved in research works and their impact on citations, h-index, cross reference citation and publications. It also analyses the top ten departments and faculty based on publication, citation and h-index of the Indian Institute of Science. Five hundred fifty-three faculty members published 40018 publications in Solidstate and Structural Chemistry Unit has 3130 publications with 140789 citations. Dr Jyothsna Rani Komaragiri from Centre for High Energy Physics Department has 1052 publications in his/her credit and having the h- index of 114.
Keywords: Indian Institute of Science; Indian research information network system; H-Index; Faculty profile; Research management system